Sistem Pendukung Keputusan Pemilihan Varietas Bibit Padi Unggul Menggunakan Metode TOPSIS (Studi Kasus BPP Cibeureum Kota Tasikmalaya) - Yayas Husni Mubarok; Cepi Rahmat Hidayat; Yusuf Sumaryana (Jurnal Teknologika, 2024)
Agriculture plays a central role in the development of Indonesia, with a significant portion of the population relying on this sector, particularly as rice farmers. To maintain food security and support sustainable agriculture, increasing the productivity and quality of rice production is crucial. However, the diversity of rice varieties poses a challenge in selecting optimal seeds for farmers, which can affect their harvest yields and well-being. Therefore, this research aims to identify and recommend superior rice varieties in the Balai Penyuluhan Pertanian (BPP) Cibeureum area of Tasikmalaya City using the TOPSIS method. Additionally, a web-based decision support system has been designed to facilitate the selection process for rice seeds. The research findings indicate that the best rice seed varieties are Cakrabuana, Inpari 42, and Inpari 36. The web-based decision support system was successfully developed using the TOPSIS method, and user response evaluations showed an application feasibility rate of 71.9%. Furthermore, the accuracy, completeness of information, and trust in criteria and alternatives reached 75.21%, demonstrating significant potential contribution to optimal decision-making in selecting rice seed varieties.